Tinjauan Teknis dan Ekonomi Beberapa Bahan Koagulan untuk Pengolahan Air Minum dengan Air Kali Progo Sebagai Air Baku pada Spam Regional Yogyakarta, Sleman dan Bantul - Sindu Nuranto; Syaukat Ali (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
As we understand together that today has begun to decrease the utilization of deep well water and water springs as an alternative source of water in the PDAM, this is due to environmental conditions that have undergone many changes so that our environment has been experiencing a lot of carrying capacity. The selection of deep well water is preferred because the water quality is relatively better than the surface water. This condition causes PDAM to choose surface water such as river water as raw water, such as Progo water which is now used as alternative water for PDAM Kota Yogyakarta, PDAM Sleman and Bantul. Characteristics of surface water are generally poorer than ground water, this is due to more possibilities of contamination with pollutants resulting from human activities such as industry, agriculture and even natural events such as rain. It is physically easy to see that the surface water is generally cloudy compared to groundwater, since surface water generally contains mud and larger suspended particles. To reduce the mud content and suspended particles can be used coagulant material. There are many types of coagulant materials that we know such as alum (Alumunium Sulfate, Sodium Aluminate, Ferro Sulphate, Ferric Sulphate, Ferric Chloride, Lime and others). Technically coagulant capable of decreasing turbidity up to 0 NTU is Al2(SO4)3, combination between NaAlO2 and PAC, and combination between Fe (SO4) and PAC. Economically the cheapest coagulant is alum, with the optimum dose not much different but the purchase price is much cheaper than other types of coagulant.